Structure and expansion law of H ii regions in structured molecular clouds. Issue 2 (16th May 2019) - Zamora-Avilés, Manuel; Vázquez-Semadeni, Enrique; González, Ricardo F; Franco, José; Shore, Steven N; Hartmann, Lee W; Ballesteros-Paredes, Javier; Banerjee, Robi; Körtgen, Bastian
Abstract: We present radiation-magnetohydrodynamic simulations aimed at studying evolutionary properties of H ii regions in turbulent, magnetized, and collapsing molecular clouds formed by converging flows in the warm neutral medium. We focus on the structure, dynamics, and expansion laws of these regions. Once a massive star forms in our highly structured clouds, its ionizing radiation eventually stops the accretion (through filaments) towards the massive star-forming regions. The new overpressured H ii regions push away the dense gas, thus disrupting the more massive collapse centres. Also, because of the complex density structure in the cloud, the H ii regions expand in a hybrid manner: they virtually do not expand towards the densest regions (cores), while they expand according to the classical analytical result towards the rest of the cloud, and in an accelerated way, as a blister region, towards the diffuse medium. Thus, the ionized regions grow anisotropically, and the ionizing stars generally appear off-centre of the regions. Finally, we find that the hypotheses assumed in standard H ii -region expansion models (fully embedded region, blister-type, or expansion in a density gradient) apply simultaneously in different parts of our simulated H ii regions, producing a net expansion law ( R ∝ t α, with α in the range of 0.93–1.47 and a mean value of 1.2 ± 0.17) that differs from any of those of the standard models.